Vertical Integration in Visual System Education: A New Educational Experience - Simin Mahakizadeh; Saleheh Khorasani; Leila Sadati; Mohsen Arabi; Fatemeh Kermanian (Strides in Development of Medical Education)
Background: The purpose of the medical curriculum is to train up-to-date physician who can safely and effectively diagnose diseases and increase the health of society.Objectives: We designed a visual system anatomy educational course to investigate the effect of the “extending the teaching of the basic science throughout the curriculum” strategy, on the level of satisfaction and learning of medical student’s anatomy knowledge.Methods: This study was an interventional, in descriptive type, done in visual system anatomy educational course and designed in four training sessions consisted of: 1. A 15 multiple choice questions pre-course online test, distributing lesson plans and related educational videos, 2 and 3.training sessions in which education content by using cadaver and other teaching aids such as moulage and slides were presented; 4.Discussion, post-test holding and distribution of satisfaction questionnaire. The overall pre-intervention and post-intervention data were analyzed using Kolmogorov–Smirnov test and paired t-test in Statistical Package for the Social Sciences (SPSS) software. P-value less than 0.05 was considered as statistical significance.Results: Based on the results of the final exam, correct answer percentage to each question (CAP) of post-intervention were higher than the CAP of the pre-intervention. The statistical analysis also indicated that there was significant difference in the mean of CAPs between the two tests (p>0.01).Conclusion: It seems that proposing a new curriculum and including basic anatomy sessions in clinical training courses can help students to review basic science concepts and apply them in developing clinical skills and ultimately safe patient care.